Investigation of turbulent thermal-hydraulic behaviors of a heat exchanger tube with U-cut twisted-tape - K. Wongcharee; V. Chuwattanakul; S. Chamoli; N. Maruyama; M. Hirota; S. Eiamsa-ard (Case Studies in Thermal Engineering)
This study examines the influences of U-cut twisted tapes (U-TTs) on thermal-hydraulic behaviors in a circular tube with uniform heat flux. The geometric parameters studied include six U-cut ratios (s/t = 0.5, 1.0, 1.5, 2.0, 2.5, and 3.0) and two twist ratios (y/w = 3.5 and 4.0). Experimental results revealed that their U-cut ratios highly influenced heat transfer enhancement. U-TTs with U-cut ratios (s/t) of 0.5, 1.0, 1.5, and 2.0 achieved higher Nusselt numbers than conventional twisted tapes (TTs). In contrast, U-TTs with larger U-cut ratios (s/t = 2.5 and 3.0) showed reduced Nusselt numbers. However, friction losses with all U-TTs were consistently higher than those with TTs. Due to their excellent heat transfer enhancement, U-TTs with s/t ratios of 0.5 and 1.0 exhibited significantly higher thermal performance factors (TPF) than conventional TTs. The highest TPF, 1.28, was achieved by U-TTs with an s/t ratio of 0.5 and a y/w of 3.5 at a Reynolds number of 6000.